Sodium nitroprusside induces H‐Ras depalmitoylation and alters the cellular response to hypoxia in differentiated and undifferentiated PC12 cells. (19th August 2019) - Goloshvili, Galina; Barbakadze, Tamar; Mikeladze, David
Abstract : Ras‐GTPases regulate many central signalling pathways in the cell. Hypoxia induces nitrosative/oxidative stress and dysregulates Ras‐dependent downstream processes. H‐Ras possesses two cysteine residues (C181 and C184) in the C‐termini, which are palmitoylated once or twice. Palmitoylation is sufficient for promoting stable plasma membrane localization. We hypothesized that high concentrations of hypoxia‐formed nitric oxide could induce terminal cysteine S‐nitrosylation, followed by depalmitoylation and H‐Ras mislocalization. We investigated the action of a 100‐μM nitric oxide‐donor (sodium nitroprusside [SNP]) and a 100‐μM palmitoylation inhibitor (2‐bromopalmitate) on the distribution of membrane‐bound S‐nitrosylated and palmitoylated H‐Ras under hypoxic/normoxic conditions in undifferentiated/differentiated pheochromocytoma (PC12) cells. We found that under normoxic conditions, SNP increases membrane‐bound H‐Ras nitrosylation only in differentiated cells, whereas under hypoxic conditions, SNP stimulates H‐Ras nitrosylation in both differentiated and undifferentiated cells. SNP greatly decreases the palmitoylation of H‐Ras under hypoxic conditions in both undifferentiated and differentiated cells, while under normoxic conditions, the effect of SNP is more negligible. Furthermore, Western blot analyses have shown that SNP decreases ERK phosphorylation under hypoxic conditions, in parallel with an elevation in hypoxia‐induced factor activity and intracellular succinate concentration. We propose that high concentrations of hypoxia‐formed nitric oxide can nitrosylate H‐Ras terminal cysteines, which induce H‐Ras activity dysregulation and alter the cellular response to hypoxia. Significance of the study: To our knowledge, these observations may be important for cancer prevention and therapy because cancer is one of the most prevalent disorders caused by the misregulation of Ras activity by a redox agent. Oncogenic activation of the H‐Ras gene has been found in a wide variety of neoplastic transformations, and thus, investigation of the redox regulation of H‐Ras activity is significant for cancer research as well.